Design and implementation of audio-visual learning media for volleyball passing and serving techniques in junior high school - Budiman, Indra Adi; Priyono, Ali; Rustandi, Endi (Jurnal Keolahragaan, 2024)
One of the main challenges in physical education learning is the limited availability of appropriate and interesting learning media for students. This research aimed to develop audio-visual learning media products in class VIII junior high school PE subjects on specific motion material for variations in upper passing, lower passing variations, upper service variations, and lower service variations in volleyball games. The research was conducted as development research adopted the Borg & Gall model: preliminary study, planning stage and initial research product development, expert validity test stage and product revision, small- and large-scale tests, effectiveness test and distribution of learning media products. Validation of learning media development is carried out by learning material experts, learning media experts, and learning media design experts. Following the expert validation of the learning content and material by subject matter experts, the validation of the learning media by media specialists, and the validation of the learning media design, further validation conducted by an online questionnaire to gather further feedback and insights. The results were obtained in the form of audio-visual learning media products that were tested to large groups receiving a validation score of 93% from learning material experts, 94% from learning media experts, and 95% from learning media design experts. For the effectiveness test, pre and post-tests on improving volleyball passing and serving skills has done and obtained the experimental class obtained a gain value of 0.62 and the control class obtained a gain value of 0.28. This research concluded that the use of audio-visual learning media in physical education showed positive results in improving understanding, motivation, and learning outcomes of volleyball games. With the right support, this media can be an effective tool to enrich the learning experience and support the achievement of physical education goals.